The effectiveness of group training for reciprocal behavior analysis on the self-efficacy among school counselors - Raziye Keramati; Mehrangiz ShoaKazemi; Farhad Tanhaye Reshvanloo; Simin Hosseinian (Gonabad University of Medical Sciences, 2015)
The aim of the present research was to assess the effectiveness of group training in transactional analysis on the self-efficacy Dimensions of the school counselors. The research method was semi-empirical with pretest- posttest which was held on the control group. Research statistic population included School` s counselors in Bojnourd city in the year 2011. In the first step 77 people of these counselors were selected randomly and complete the Sherer & Maddux (1982) Self-efficacy scale. Then 28 people (21 female and 7 male) that had scored low were randomly placed in control and experimental groups. Experimental interference (group training in transactional analysis) was held on the experimental group in ten sessions, each session lasted ninety minutes twice a week. At the end of the educational program, post-test was held in both groups after one week. Data analyzed by multivariate covariance (MANCOVA). The results indicated that there is no significant difference between two groups in dimensions of self-efficacy.